Determinants of Preschool Teachers' Attitudes towards Teaching - FLORENCE NJERI KINUTHIA; Donald Kisilu Kombo; Maureen Mweru (Sustainable Programs to Reduce Educational and Avocational Disadvantages (SPREAD), 2013)
This study sought to investigate determinants of pre-school teachers' attitudes towards teaching in Thika Municipality, Kenya. The concern to stakeholders was the negative attitudes of the pre-school teachers towards teaching. Such a concern called for investigation. To accomplish this task, a descriptive survey design and Ex-post facto design were used. A total of 53 pre-school teachers and 12 administrators participated in the study. A simple random technique and purposive sampling were employed to identify study samples. In addition, questionnaires and interviews were used to collect data. The statistical procedures were carried out using the statistical package for social sciences (SPSS). Qualitative and quantitative techniques were employed in order to analyse the obtained data. The study revealed there were still low levels of training among pre-school teachers, teachers with few years of teaching experience were the ones involved in teaching in the pre-schools and teachers in public pre-schools were more positive towards their job than their colleagues in private schools. Among the recommendations were that pre-school teachers work under the Ministry of Education and an attempt be made to improve the retention level of teachers. Administrators should also work on modalities of motivating their teachers.